Improving the hole transport performance of perovskite solar cells through adjusting the mobility of the as-synthesized conjugated polymer. Issue 10 (18th February 2021) - Liu, Wenbo; Ma, Yiming; Wang, Zongrui; Mu, Zhao; Gao, Weibo; Fan, Weijun; Li, Wei-Shi; Zhang, Qichun
Abstract : The as-fabricated PSC with the as-synthesized HTL P5NH maintained a very high fill factor of 83.1% with an efficiency of 18.1%. Abstract : Perovskite solar cells (PSCs) have achieved great success in recent years. However, one obstacle that impedes the industrialization of PSCs is the lack of a suitable dopant-free hole transport layer (HTL). An effective strategy to achieve suitable HTLs with satisfying properties is to amend the conjugated frameworks in the existing organic semiconductors. The precision of this strategy requires improving the targeted properties without greatly affecting other important optical and electrical features. Here, we have presented a simple and facile method that could solely improve the mobility of the as-synthesized polymeric HTL without greatly affecting other important electrical properties. By elaborately combining the repeat units, the mobility of the polymer has been improved while other properties of the modified polymer almost remained unchanged in a complicated photoelectric environment (as the HTL for PSCs). The as-fabricated PSC with the as-synthesized HTL maintained a very high fill factor of 83.1% with an efficiency of 18.1%. Our work proposed a method for meticulously controlling the single property of the polymeric HTL without affecting other properties, proving that structural engineering is feasible to achieve the desired functional materials for practical devices.